Scaffolded Reading to Improve Student Reading Performance at SMPN 5 Kodi Utara - Mone, Lukas Pati (STKIP Harapan Bima, 2023)
This study aims to describe whether Scaffolded Reading can improve the reading achievement of grade I students of SMP Negeri 5 Kodi Utara for the 2022/2023. The research method applied in this study is classroom action research (CAR) with a collaborative action research design where the subject of this study is grade I students of SMP Negeri 5 Kodi Utara. The author only focuses on the application of Scaffolded Reading to improve student reading achievement. Data is collected through quantitative and qualitative data. Quantitative data were obtained from the reading scores of pretest and posttest students. Then, the techniques used to collect the data are; The test consists of 30 items with 4 options and is categorized as multiple choice. Then qualitative data were obtained from observation sheets and questionnaires. The findings of this study show that there is a progression in students' reading achievement and improvement. It can be seen from the average score of the pretest is 65.95. and the average posttest score was 83.30. In addition, there were 9 students or 45% of the 25 students who passed the Minimum Completeness Criteria (KKM) in the pretest. Meanwhile, in the first cycle there were 18 students or 90% of the 25 students. Then, from the observation sheet, the results showed that more students responded well to reading independence in teaching reading. Based on the results of percentage data in questionnaires such as Strongly Agree is 18.00%, Agree is 15.60%, UndecidedÂ is 4.35%, Disagree is 1.30%, and Strongly Disagree is 0.55%. The authors conclude that students' reading achievement improved very well in learning to read English